Espacement in Cinchona Plantations - Chaturvedi, M. D. (Indian Forester, 1952)
While the technique adopted in raising Cinchona in the South leaves little to be desired, the deleterious effects of congestion on the growth of trees would hit the eye of the most casual visitor. Well-developed trees which happen to possess the growing space, they have, by accident and not by design, provide an indication of the espacement to be aimed at. Pending scientific experimentation, the existing spacing of 4 ft. by 4 ft. should be stepped up to 8 ft. by 8 ft. This will not only ensure better development, but would also reduce the planting costs to at least about a third.